ChemInform Abstract: Electrochemical Behavior of SiO as an Anode Material for Na‐Ion Battery. Issue 30 (July 2015) - Shimizu, Masahiro; Usui, Hiroyuki; Fujiwara, Kohei; Yamane, Kazuya; Sakaguchi, Hiroki
Abstract Commercial SiO is ball milled and vapor deposited to achieve an active Na‐ion battery thick‐film anode without the need for a binder or conductive additive.